USAG-1 Inhibition: Paving the Way for Lab-Grown Tooth Regeneration in Modern Dentistry - Sajda Khan Gajdhar (Oral Sphere Journal of Dental and Health Sciences, 2025)
Tooth loss is a prevalent health issue that traditional solutions address through either prosthodontic restorations or dental implants. Laboratory-produced bioengineered teeth are no longer a scientific speculation, as regenerative medicine continues to make innovative progress. The critical advancement within this research area relies on USAG-1 (Uterine Sensitization Associated Gene-1) gene suppression which blocks tooth development. Scientists have shown that USAG-1 inhibition leads to supernumerary tooth growth through recent studies thereby creating a modern dental therapeutic option. The investigative analysis reviews existing knowledge about lab-grown teeth to explore USAG-1 regulation of dental tissue regeneration together with potential treatments despite implementation barriers.